2021
DOI: 10.1111/liv.14935
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatic involvement in the clinical spectrum of A20 haploinsufficiency

Abstract: Background & Aims Secondary to tumour necrosis factor‐alpha induced protein 3 (TNFAIP3) mutations, A20 haploinsufficiency (HA20) is a recently described autoinflammatory disease with clinical features similar to those of Behçet's and Crohn's diseases but with a constantly expanding clinical spectrum. Here, we describe HA20 liver involvement in three new patients from the same family. Methods We retrospectively assessed clinical, biological and/or histological findings for eight patients over three generations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The parallels between skin fibrosis in A20 +/− mice and in patients with SSc are underscored by a remarkable degree of gene regulation congruency between mouse and SSc, with 50% of genes sharing deregulated expression in both. Of potential relevance, it was recently reported that some patients with heterozygous loss of function mutations in the TNFAIP3 develop fibrosis in the liver 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The parallels between skin fibrosis in A20 +/− mice and in patients with SSc are underscored by a remarkable degree of gene regulation congruency between mouse and SSc, with 50% of genes sharing deregulated expression in both. Of potential relevance, it was recently reported that some patients with heterozygous loss of function mutations in the TNFAIP3 develop fibrosis in the liver 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, liver function revealed abnormally elevated transaminases, excluding other liver diseases. Recent research reported that patients with HA20 develop chronic liver involvement due to hepatic fibrosis, hepatocyte injury, and/or inflammatory T lymphocyte infiltrates with moderate NF-κB and/or NLRP3 staining ( 15 ). This indicates that HA20 may be present in patients who have multiple concurrent autoimmune diseases, Behcet’s-like symptoms, and unexplained liver function abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, genetic analyses appear also useful to diagnose inflammatory systemic conditions and those associated with a high risk of liver failure. Deshayes et al described the frequent liver involvement in patients with A20 haploinsufficiency, a dominant auto‐inflammatory systemic disorder caused by tumour necrosis factor‐alpha‐induced protein 3 ( TNFAIP3 ) mutations 18 …”
Section: Figurementioning
confidence: 99%